2018
DOI: 10.1111/crj.12914
|View full text |Cite
|
Sign up to set email alerts
|

Does the 2017 revision improve the ability of GOLD to predict risk of future moderate and severe exacerbation?

Abstract: Low FEV was an important risk factor for future exacerbations. Downstaging of C1/D1 patients caused heterogeneity in A/B with including patients with low and high risk of future exacerbation. This resulted in a low discriminative power of GOLD 2017 regarding the risk of future exacerbation in groups A and B. This may cause underestimation of disease severity and inadequate treatment especially in A/B patients with low FEV .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, this 1-year follow-up study also proposed that prospective annual experience of moderate-to-severe exacerbation was higher in the DB group than in the BB group [22] . Similarly, the retrospective study mentioned above showed that C1/D1 patients had a significantly higher risk of moderate and severe exacerbation in the next year compared to A/B patients according to GOLD 2011 [21] . The worse pulmonary function and more severe symptoms might be related to the poorer short-term prognosis in the DB group.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Moreover, this 1-year follow-up study also proposed that prospective annual experience of moderate-to-severe exacerbation was higher in the DB group than in the BB group [22] . Similarly, the retrospective study mentioned above showed that C1/D1 patients had a significantly higher risk of moderate and severe exacerbation in the next year compared to A/B patients according to GOLD 2011 [21] . The worse pulmonary function and more severe symptoms might be related to the poorer short-term prognosis in the DB group.…”
Section: Discussionmentioning
confidence: 53%
“…[ 19 ] In a retrospective database analysis involving a national cross-sectional observational survey in China, some of the changes in demography and clinical characteristics of the new group A/B were associated with a high risk of exacerbation and/or mortality. [ 20 ] Erol et al [ 21 ] conducted a retrospective study recruiting 225 patients from COPD outpatient clinics and showed that the risk of future moderate and severe exacerbations was higher in 2017 GOLD groups A and B than in 2011 GOLD groups A and B. These results seem to suggest that GOLD 2017, with down staging of patients, may undervalue the severity and exacerbation risk of patients reclassified to group B, resulting in inadequate treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation